Divergent anthropocentrisms: an Inuit exercise of self-determination via living resource management in an international context - Boyer, Kurtis (Author); Murphy, Michael (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2010)
Since the establishment of self-government in Nunavut, the Inuit have gained domestic self-determination over the management of important living resources such as the polar bear. By exercising self-determination, the Inuit have been better able to realize the maximum economic utility of these resources by pursuing their commodification in international markets. Recently, however, the ability of the Inuit to use the international market as a medium for economic development has been constrained by environmental campaigns that oppose the commodification of the polar bear as a hunting trophy. This paper examines the impact of these international forces on Inuit self-determination, and on the capacity of Inuit to achieve their longer term economic development goals. Using polar bear management as a case study, I argue that in order to achieve their longer-term economic development objectives in relation to living resource management, the Inuit must employ a more pragmatic and strategic approach to the pursuit of economic opportunities in the international marketplace. In order to advance their pursuit of economic self-determination, I argue that the Inuit must seek to establish more cooperative relationships with international actors such as environmental NGOs, and with respect to the commercial development of Arctic wildlife, establish a common set of goals that are based on a shared anthropocentrism. --P.ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1736488